Azide-Based High-Energy Metal-Organic Frameworks with Enhanced Thermal Stability - Serafini, D; Herrera-Urbina, F; Singh, D; Enríquez-Montenegro, J; Manquián-Villalobos, C; Fritz, R; Chi-Duran, I (American Chemical Society, 2019)
We describe the structure and properties of [Zn(C6H4N5)N3]n, a new nonporous three-dimensional high-energy metal-organic framework (HE-MOF) with enhanced thermal stability. The compound is synthesized by the hydrothermal method with in situ ligand formation under controlled pH and characterized using single-crystal X-ray diffraction, elemental analysis, and Fourier transform infrared. The measured detonation temperature (Tdet = 345 °C) and heat of detonation (Î"Hdet =-0.380 kcal/g) compare well with commercial explosives and other nitrogen-rich HE-MOFs. The velocity and pressure of denotation are 5.96 km/s and 9.56 GPa, respectively. Differential scanning calorimetry analysis shows that the denotation of [Zn(C6H4N5)N3]n occurs via a complex temperature-dependent mechanism. Copyright © 2019 American Chemical Society.